Guidelines for communicating about bats to prevent persecution in the time of COVID-19. (August 2020) - MacFarlane, Douglas; Rocha, Ricardo
Abstract: While the current COVID-19 pandemic continues to wreak havoc on human health and national economies, conservationists are struggling to prevent misguided persecution of bats, which are misleadingly being blamed for spreading the disease. Although at a global level, such persecution is relatively uncommon, even a few misguided actions have the potential to cause irrevocable damage to already vulnerable species. Here, we draw on the latest findings from psychology, to explain why some conservation messaging may be reinforcing misleading negative associations. We provide guidelines to help ensure that conservation messaging is working to neutralize dangerous and unwarranted negative-associations between bats and disease-risk. We provide recommendations around three key areas of psychological science: (i) debunking misinformation; (ii) counteracting negative associations; and (iii) changing harmful social norms. We argue that only by carefully framing accurate, honest, and duly contextualized information, will we be able to best serve society and present an unbiased perspective of bats. We hope this guidance will help conservation practitioners and researchers to develop effective message framing strategies that minimize zoonotic health risks and support biodiversity and its associated ecosystem services. Highlights: Bats risk persecution due to misguided fears associated with COVID-19. Conservation messaging may reinforce negative links between wildlife and zoonoses. Psychological science is key for effective conservation message framing. Messaging should debunk misinformation while counteracting negative associations. Framing should be accurate, honest, and highlight desirable social norms.